Resistance and Oppression in J.K. Rowling’s The Ickabog - Aryaputra, Maulana Andhika; Masitoh, Siti (Journal of Literature, Linguistics, & Cultural Studies, 2024)
This study aimed to discuss the oppression experienced by the Cornucopians and how the main characters and any other characters countered the oppressors in The Ickabog. This study was categorized into literary criticism using an objective approach by applying Young's Five Faces of Oppression theory (1990) and supported by Scott's Concept of Resistance (2000). The data were taken from words, phrases, sentences, and paragraphs in the novel The Ickabog by J.K. Rowling. The data were identified and interpreted, and then the conclusion was drawn. There were two results from this study. First, the characters of The Ickabog, the Cornucopians, suffered from oppression. Most of them have been oppressed by their government. They are forced to hand over what they have to the government. Otherwise, they can be arrested or even killed. Second, the novel's main characters, Daisy Dovetail and Bert Beamish, are accompanied by some characters successfully performing the resistance against the oppressors. The form of their resistance is done openly or closely. In summary, Daisy and Bert, alongside the other Cornucopians, can finally liberate themselves from their oppressive rulers, and Cornucopia becomes a peaceful country once again. The researcher suggested that further researchers analyze The Ickabog through other approaches and theories, such as Marxism, psychoanalysis, or feminism.